2021
DOI: 10.1186/s12889-021-10403-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with overweight and obesity in selected health areas in a rural health district in Cameroon: a cross-sectional analysis

Abstract: Background Overweight and obesity are major public health problems worldwide, with projections suggesting a proportional increase in the number of affected individuals in developing countries by the year 2030. Evidence-based preventive strategies are needed to reduce the burden of overweight and obesity in developing countries. We assessed the prevalence of, and factors associated with overweight and obesity in selected health areas in West Cameroon. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
5
14
3
Order By: Relevance
“…General obesity alone and combined obesity were more likely among those with any form of formal education; significance was observed with general obesity alone. This is in line with the report of Simo et al [ 26 ] but contrary to the report of lower risk of obesity among educated women [ 21 ]. Our finding may be attributed to consumption of energy dense foods which according to Simo et al [ 26 ] may be a function of improved economic status associated with higher education.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…General obesity alone and combined obesity were more likely among those with any form of formal education; significance was observed with general obesity alone. This is in line with the report of Simo et al [ 26 ] but contrary to the report of lower risk of obesity among educated women [ 21 ]. Our finding may be attributed to consumption of energy dense foods which according to Simo et al [ 26 ] may be a function of improved economic status associated with higher education.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the report of Simo et al [ 26 ] but contrary to the report of lower risk of obesity among educated women [ 21 ]. Our finding may be attributed to consumption of energy dense foods which according to Simo et al [ 26 ] may be a function of improved economic status associated with higher education. That education improves literacy and understanding, promotes better life style choices and helps the development of good health habits depends on the ability of the individual to live by what has been learnt.…”
Section: Discussionsupporting
confidence: 92%
“…Older age was consistently associated with a greater prevalence of overweight and obesity, consistent with past studies in Uganda [13,21] and other sub-Saharan African countries [22][23][24][25]. Female sex was also associated with higher probability of overweight and obesity.…”
Section: Discussionsupporting
confidence: 87%
“… 8 A South African study has reported that 56%, 49% and 75% of white men, African men and women were overweight or obese, respectively. 9 Obesity prevalence amongst Africans was attributed to cultural attitudes towards fatness. 8 It was found that culture affects body image and size perceptions from an early age and that exclusive body shape and weight ideals are recognised amongst different cultures.…”
Section: Introductionmentioning
confidence: 99%